تسجيل نوع جديد من الهدبيات Trichophyra piscium (Family Suctoria:Genus Trichophera) المتطفلة على الأسماك في بحيرة سد 16 تشرين، اللاذقية - سورية - ديوب, أمل (Latakia University Journal -Biological Sciences Series, 2018)
The present study aimed to investigate any new species of parasitic ciliate infected fishes in the Lake of 16 Tishreen Dam, and to determine their prevalence rate, and its pathological effects on fishes. Fishes samples are: Common carp( Cyprinus carpio L. ), Varicorhinus damascinus, and Garra rufus, and Tilapia zillii , and Liza abu, were collected randomly from the Lake, one time / month, during the period from December/2013 to November/2013. The total number of collected fishes was 242 individuals. Through microscopic examination of mucus smears which were taken from the gills of fishes, we could record a new species of parasitic ciliates, which is Trichophyra piscium , It was infected only Tilapia zillii fish, , The general rate of infection was 9.91%. and the Infection was limited in summer only. This species recoded as new species of ciliates infecting fishes in the 16 Tishreen Dam for the first time in Syria. بهدف التقصي عن أنواع جديدة من الهدبيات الطفيلية الخامجة للأسماك في بحيرة سد 16 تشرين، وتحديد معدل انتشارها، وتأثيراتها الإمراضية على حياة الأسماك. جمعت عينات أسماك الكارب العادي.Cyprinus carpio L., والأصفر الدمشقي Varicorhinus damascinus, والتريس الزيتي Garra rufus, والمشط المرموري Tilapia zillii, والبوري Liza abu عشوائياً من البحيرة، بمعدل مرة واحدة /شهرياً, خلال الفترة الممتدة من كانون الثاني/ 2013, وحتى كانون الأول/ 2013 . وبلغ عددها الأسماك 242سمكة. أمكن من خلال الفحص المجهري للكشطات المخاطية المأخوذة عن غلاصم الأسماك المدروسة. تسجيل نوع جديد من الهدبيات الطفيلية على غلاصم أسماك المشط المرموري هو Trichophyra piscium، بمعدل إصابة 9.91 %. ظهرت الإصابة في فصل الصيف فقط. وهو يسجل لأول مرة كطفيلي هدبي جديد متطفل على الأسماك في بحيرة سد 16 تشرين.